Five new species of Amicromias Reitter, 1912 from Greece (Coleoptera: Curculionidae: Entiminae: Omiini) - Borovec, Roman; Kakiopoulos, George; Germann, Christoph (Zootaxa, 2017)
Five new species of Amicromias Reitter, 1912 from Greece are described, illustrated and compared with closely related species: A. cunevi sp. n., A. osellai sp. n., A. platanegrachei sp. n., A. thracicus sp. n. and A. yunakovi sp. n. The presently unknown male of A. intermedius Yunakov, 2005 is described. Amicromias fodori Yunakov, 2005 and A. intermedius Yunakov, 2005 are recorded for the first time from Greece. All Greek species of the genus are keyed and distributions are mapped.